Unsedated or On-Demand Minimally Sedated Water-Aided Outpatient Colonoscopy in Colorectal Cancer Screening and Surveillance: A Step Forward or Backward? Experience from Daily Practice in a Regional (Nonacademic) Hospital - Stijn Arnaert; Diederik Persyn; Mike Cool; Guy Lambrecht; Guido Deboever (Diagnostics)
Background: By using optimal insertion techniques with water infusion and dynamic position changes, pain during colonoscopy is greatly reduced and the procedures can usually be performed without sedation. We investigated whether the excellent results with water-aided colonoscopy reported by experts are reproducible in daily practice in a regional hospital. Methods: During the year 2023, 500 consecutive outpatients 50–75 years old presenting for colorectal cancer screening and surveillance could choose between unsedated or on-demand minimally sedated colonoscopy, moderate sedation with midazolam, or deep sedation with propofol. A total of 57% opted for unsedated colonoscopy, and of those patients, 250 consecutive patients were included. The primary outcome was the feasibility of the procedure. Cecal intubation rate (CIR), pain scores, use of midazolam, and willingness to repeat future procedures in the same way were registered periprocedural. Additional outcomes were cecal intubation time (CIT), detection rate of lesions, polyp resection rate, rate of adequate bowel preparation, and volume of water aspirated during insertion. Results: 250 consecutive sedation-free or on-demand minimally sedated water-based colonoscopies were analyzed. The CIR was 98%. A total of 96.5% completed without sedation and 5% of the procedures were perceived as moderately painful, but none had severe pain. The willingness to repeat was 97%. The mean CIT was 8.2 min. Conclusions: Using water-aided insertion techniques, comfortable sedation-free, or on-demand minimally sedated colonoscopy in daily practice in a regional hospital is feasible in the vast majority of patients presenting for colorectal cancer screening and surveillance, and the willingness to repeat is very high.